Effect of intracanal medications on the interfacial properties of reparative cements - Andrea Cardoso Pereira; Mariana Valerio Pallone; Marina Angélica Marciano; Karine Laura Cortellazzi; Marcos Frozoni; Brenda P. F. A. Gomes; José Flávio Affonso de Almeida; Adriana de Jesus Soares (Restorative Dentistry & Endodontics)
ObjectivesThe purpose of the present study was to evaluate the effect of calcium hydroxide with 2% chlorhexidine gel (HCX) or distilled water (HCA) compared to triple antibiotic paste (TAP) on push-out bond strength and the cement/dentin interface in canals sealed with White MTA Angelus (WMTA) or Biodentine (BD).Materials and MethodsA total of 70 extracted human lower premolars were endodontically prepared and randomly divided into 4 groups according to the intracanal medication, as follows: group 1, HCX; group 2, TAP; group 3, HCA; and group 4, control (without intracanal medication). After 7 days, the medications were removed and the cervical third of the specimens was sectioned into five 1-mm sections. The sections were then sealed with WMTA or BD as a reparative material. After 7 days in 100% humidity, a push-out bond strength test was performed. Elemental analysis was performed at the interface, using energy-dispersive spectroscopy. The data were statistically analyzed using analysis of variance and the Tukey test (p < 0.05).ResultsBD presented a higher bond strength than WMTA (p < 0.05). BD or WMTA in canals treated with calcium hydroxide intracanal medications had the highest bond strength values, with a statistically significant difference compared to TAP in the WMTA group (p < 0.05). There were small amounts of phosphorus in samples exposed to triple antibiotic paste, regardless of the coronal sealing.ConclusionsThe use of intracanal medications did not affect the bond strength of WMTA and BD, except when TAP was used with WMTA.